Economic and Social Relationships of Thai-Cambodian Border Communities in Chanthaburi Province - Kaewkumkong, Ampa (Kasetsart Journal of Social Sciences, 2015)
The objective of this research was to study the economic and social relationships of communities around the Thai-Cambodian border in Chanthaburi province as well as to propose policy implications for the development of the area and for the promotion of Thai-Cambodian relationships. Data were collected from documents, field research, and interviews of relevant persons. The research took place from May 2012 to August 2013. Data were analyzed using content analysis and descriptive analysis. The study found that communities around the Thai-Cambodian border in Chanthaburi province rely on each other in their everyday lives. There has been increased activity associated with both economic and social cooperation where the private sector in the area and local administration organizations play leading roles and are subsidized by the government. This is partly a result of the preparation for the Asean Economic Community which begins in 2015. This research proposes that the cultural development should be given as much importance as the development in an unbiased economy, surveillance for new security resulting from development, promotion to increase participation by the general public in development, as well as the promotion and sustainability of good relationships between Thailand and Cambodia.